Apartheid and the Making of a Black Psychologist : a memoir - Manganyi, N. C. (Wits University Press, 2016)
"This intriguing memoir details in a quiet and restrained manner what it meant to be a committed black intellectual activist during the apartheid years and beyond. Few autobiographies exploring the 'life of the mind' and the 'history of ideas' have come out of South Africa, and N Chabani Manganyi's reflections on a life engaged with ideas, the psychological and philosophical workings of the mind and the act of writing are a refreshing addition to the genre of life writing. Starting with his rural upbringing in Mavambe in Limpopo province in the 1940s, Manganyi's life story unfolds at a gentle pace, tracing the twists and turns of his journey from humble beginnings to Yale University in the USA. The author details his work as a clinical practitioner and researcher, as a biographer, as an expert witness in defence of opponents of the apartheid regime and, finally, as a leading educationist in Mandela's Cabinet and in the South African academy. Apartheid and the Making of a Black Psychologist is a book about relationships and the fruits of intellectual and creative labour. In it, Manganyi describes how he used his skills as a clinical psychologist to explore lives both those of the subjects of his biographies and those of the accused for whom he testified in mitigation; his aim always to find a higher purpose and a higher self."--Publisher description.